Comparative analysis of the frequency of postoperative intrauterine adhesions with classical and modified hysteroscopic metroplasty - Y.L. Kalitsynska; I.Z. Gladchuk; D.O. Hryhurko (Репродуктивная эндокринология)
Background. Treatment of women with RPL-syndrome (recurrent pregnancy loss), which is caused by intrauterine septum, involves hysteroscopic metroplasty. However, the main drawback of these methods is the risk of formation of the intrauterine adhesions in 35–50% of patients in the postoperative period. Modern methods of preventing the formation of postoperative intrauterine adhesions are not always effective. Objectives. To conduct a comparative analysis of the postoperative intrauterine adhesions frequency after proposed and traditional electrosurgical hysteroscopic metroplasty. Materials and methods. 138 patients with primary miscarriage (RPL-syndrome) and/or premature birth who had intrauterine septum and were operated on between 2016 and 2021 participated in the study. The main group consisted of 88 patients aged 27.52 ± 1.59 years who were performed hysteroscopic metroplasty according to the proposed modified technique. The comparative group consisted of 50 patients at the age of 28.21 ± 1.65 years that get surgical treatment according to the classical method of hysteroscopic metroplasty. The effectiveness of operations was evaluated using the «Menstrual blood loss assessment» scale (order of the Ministry of Health of Ukraine No. 353 dated 04/13/2016), the 2D/3D ultrasound method, and second-look hysteroscopy data. Results. In the main group, unlike the comparison group, postoperative hypomenorrhea was 3 times less frequent and ultrasound signs of adhesions were 2.2 times less frequent; intrauterine adhesions were detected 25% less often according to second-look hysteroscopy (p < 0.05). Conclusions. The modified technique of hysteroscopic metroplasty in comparison with the traditional technique of surgery in women with RPL-syndrome helps to reduce the frequency of postoperative intrauterine adhesions by 25%. The obtained results are preliminary and require further research.